Time-dependent NIR fluorescent probe with large Stokes-shift for detecting Cys/Hcy and cell imaging. (July 2022) - Ai, Yin; Ding, Haichang; Fan, Congbin; Liu, Gang; Pu, Shouzhi
Abstract: Detection and imaging of Cysteine (Cys) and Homocysteine (Hcy) in living systems have drawn extensive attention over the years due to their significant biological role. However, few fluorescence probes have been reported to distinguish Cys and Hcy in near-infrared (NIR) range. In this paper, an original NIR Cys and Hcy fluorescent probe, namely DTRN, was synthesized. DTRN was constructed by using an acryloyl ester group as a trigger and dicyanoisophorone-derived as the fluorophore unit, it was found to emit NIR fluorescence with a 718 nm emission and have large stokes shift (∼176 nm). DTRN hold excellent performances such as ultrasensitivity (LOD = 0.09 μM), high specificity and fast response (<2 min) for Cys. Distinctly, after Hcy was introduced, the emission intensity of DTRN at 718 nm must take 20 min to reach a plateau and the LOD was found to be 0.12 μM. The sensing mechanism for Cys and Hcy in C2 H5 OH/PBS (4/6, v/v, pH = 7.4) was studied by 1 H NMR spectroscopy and HRMS. Most importantly, the ability of DTRN to detect Cys in HeLa cells had also been achieved. Graphical abstract: A NIR fluorescent probe (DTRN ) was synthesized by using acryloyl ester group as a trigger and dicyanoisophorone-derived as the fluorophore unit, it can detect Cys and Hcy emit NIR fluorescence at 718 nm and have large stokes shift (∼176 nm). Image 1 Highlights: A NIR fluorescent probe (DTRN ) with large stokes shift (∼176 nm) was synthesized. DTRN could distinguish Cys and Hcy by time-dependent fluorescence signals. The LOD for Cys and Hcy was calculated to be 0.09 μM and 0.12 μM. DTRN was successfully exploited for detecting Cys in HeLa cells.